Combined Prophylactic and Therapeutic Use Maximizes Hydroxychloroquine Anti-SARS-CoV-2 Effects in vitro - Clementi, Nicola; Criscuolo, Elena; Diotti, Roberta Antonia; Ferrarese, Roberto; Castelli, Matteo; Dagna, Lorenzo; Burioni, Roberto; Clementi, Massimo; Mancini, Nicasio (Frontiers in Microbiology, 2020)
While the SARS-CoV-2 pandemic is heavily hitting the world, it is of extreme importance that significant in vitro observations guide the quick set up of clinical trials. In this study, we evidence that the anti-SARS-CoV2 activity of a clinically achievable hydroxychloroquine concentration is maximized only when administered before and after the infection of Vero E6 and Caco-2 cells. This suggests that only a combined prophylactic and therapeutic use of hydroxychloroquine may be effective in limiting viral replication in patients.